Kecerdasan Emosi Dan Konsep Diri Dengan Problem Solving Pada Mahasiswa - Achmad Sya'dullah (IDEA: Jurnal Psikologi, 2022)
This study aims to find out whether there is a relationship between Emotional Intelligence and Self-Concept with Problem Solving in college students. The research method used is quantitative. The sample in this study was 120 students and the technique used was purposive random sampling. The data collection tools used are the Problem Solving, Emotional Intelligence and Self-Concept scales, analyzed using the SPSS (Statistical package for the Social Sciences) program. The results of the analysis obtained are r X1X2Y = 0.000 this shows a correlation between Emotional Intelligence and Self-Concept with Problem Solving. So this proposed hypothesis is accepted.